1993
DOI: 10.1115/1.2906723
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Experimental and Theoretical Study of Flow and Pressure Distributions in a Brush Seal

Abstract: A relatively simple theory is presented that can be used to model the flow and pressure distribution in a brush seal matrix. The model assumes laminar, compressible, isothermal flow and requires knowledge of an empirical constant: the seal porosity value. Measurements of the mass flow rate together with radial and axial distributions of pressure were taken on a nonrotating experimental rig. These were obtained using a 122 mm bore brush seal with 0.25 mm radial interference. The experimental data are used to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…The leakage rate of brush seals showed a slight decrease at rotating condition. Bayley and Long 4 first measured and published the axial and radial pressure distributions under the bristle tips and along the backing plate of brush seal using a non-rotating test rig. They concluded that the contact pressure between the bristle pack and rotor surface increases linearly with respect to pressure ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The leakage rate of brush seals showed a slight decrease at rotating condition. Bayley and Long 4 first measured and published the axial and radial pressure distributions under the bristle tips and along the backing plate of brush seal using a non-rotating test rig. They concluded that the contact pressure between the bristle pack and rotor surface increases linearly with respect to pressure ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The airflow goes through the porous bristle pack is subject to additional resistance forces. Bayley and Long 4 first introduced the linear Darcian porous medium model only considered the viscous flow resistance to predict the leakage flow of interference brush seal. Chew et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To widen the brush seal application in turbomachinery industry, many experimental tests and numerical models have been developed to investigate the sealing mechanisms of brush seals. Bayley and Long 13 experimentally and numerically analyzed the leakage flow and pressure distribution of typical brush seal earlier. The much smaller leakage flow rate of the zero clearance contacting brush seal was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical leakage flow rate and pressure distribution were in well agreement with the experimental data. 13 The bristle pack was dealt with the porous medium and gradually used to investigate the leakage flow of brush seal. 17 Qiu et al.…”
Section: Introductionmentioning
confidence: 99%